TSLP promoting B cell proliferation and polarizing follicular helper T cell as a therapeutic target in IgG4-related disease - Lu, Hui; Wu, Xunyao; Peng, Yu; Sun, Ruijie; Nie, Yuxue; Li, Jingna; Wang, Mu; Luo, Yaping; Peng, Linyi; Fei, Yunyun; Zhou, Jiaxin; Zhang, Wen; et al. (Journal of translational medicine, 2022)
To figure out the functions of thymic stromal lymphopoietin (TSLP) in IgG4-related disease (IgG4-RD). Plasma TSLP levels were tested by Elisa, and its receptors were detected by flow cytometry. Expressions of TSLP and TSLPR in involved tissues were stained by immunohistochemistry and immunofluorescence. Proliferation, apoptosis, and B subsets of TSLP stimulated-B cells were analyzed by flow cytometry. TSLP-stimulated B cells were co-cultured with CD4+ Naïve T cells. Signaling pathway was identified by RNA-sequencing and western blot. Anti-TSLP therapy was adapted in Lat knock-in mice (Lat, IgG4-RD mouse model). Plasma TSLP level was increased in IgG4-RD patients and was positively correlated with serum IgG4 level and responder index (RI). TSLPR was co-localized with CD19+ B cells in the submandibular glands (SMGs) of IgG4-RD. TSLP promoted B cell proliferation, and TSLP-activated B cells polarized CD4+ naive T cells into follicular helper T (Tfh) cells through OX40L. RNA-sequencing identified JAK-STAT signaling pathway in TSLP-activated B cells and it was verified by western blot. Anti-TSLP therapy alleviated the inflammation of lung in Lat mice. Elevated TSLP in IgG4-RD promoted B cells proliferation and polarized Tfh cells and might be served as a potential therapeutic target.